Nilai-Nilai Pendidikan Akidah dalam Novel “Mars Betapa Berartinya Sosok Ibu Dalam Hidupku” Karya Aishworo Ang - Aroyani, Ida; Hasanudin, Hasanudin; Husni, Husni (Bestari, 2021)
This study aims to 1) determine the values ​​of Aqidah Education in "Novel MARS How Meaningful a Mother in My Life" by Aishworo Ang. 2) find out the relevance of Aqidah Education Values ​​in the novel "MARS How Meaningful a Mother is in My Life" by Aishworo Ang with current Islamic education. The research method used by the author is content analysis. This analysis is used by the writer to reveal, understand and capture literary works. Meanwhile, data collection techniques are literature study techniques or documentation by examining various writings related to the object of research. The collected data were then analyzed using the stages of data processing, categorization, and data interpretation. After analyzing the data, the authors obtained the following conclusions: 1) The values ​​of aqidah education in the novel "MARS How Meaningful a Mother's Figure in My Life" by Aishworo Ang includes: a) Illahiyat, (a matter of divinity such as about His Essence) b ) Nubuwat, (prophetic issues, scriptures, etc.) c) Ruhaniyat (unseen problems such as spirits, angels, jinn, etc.) d) Sam'iyyat, (problems that can be known through revelation, such as barzhakh , heaven, hell and others) 2) The Relevance of Aqidah Educational Values ​​in Aishworo Ang's Novel "MARS How Meaningful a Mother's Figure is in My Life" with current Islamic education, which is in accordance with the aims of education aimed at improving the quality of Indonesian people, namely humans having faith and fearing God Almighty, this is in line with the contents of the story in the novel "MARS How Meaningful a Mother's Figure in My Life" which generally contains the values ​​of faith, including faith in Alla. h, faith in the book of Allah, faith in the Angel of God, faith in the Prophet, faith in the Last Day, and faith in the destiny of Allah.